IFN-γ and IL-4 Secretion after Stimulation of EC610 Fusion Antigens (ESAT-6-CFP-10) in Patients With Active Pulmonary TB and Latent TB - Wina Safutri; Eddy Mart Salim; Kemas Ya'kub Rahadiyanto; Muhammad Irsan Saleh; Nova Kurniati; Rachmat Hidayat; Fransisca Srioetami Tanoerahardjo (Biomedical Journal of Indonesia, 2020)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis (M.tb) and is still a major health problem in the world. Immunity against tuberculosis is very complex because it involves almost all components of the immune system. One of the cells that are responsible for cell-mediated immunity are lymphocytes, especially T helper lymphocytes are divided into Th1 (proinflammatory cytokines IFN-γ) and Th2 (anti-inflammatory cytokine IL-4). EC610 fusion antigens (ESAT-6-CFP-10) is a peptide containing a specific antigen M.tb. Order to determine the differences between the secretion of IFN-γ and IL-4 after stimulation EC610 fusion antigens (ESAT-6-CFP-10) in patients with active pulmonary TB and latent TB.Research with a quasi-experimental design in laboratory in vitro in patients with active pulmonary tuberculosis group of 21 samples and 28 samples of latent TB. Venous blood sampling in vitro anticoagulants heparin and PBMCs isolated using a Ficoll-Paque ™, then cultured with antigen fusion EC610 for 24-72 hours with a CO2 incubator at a temperature of 370 C. The levels of IFN-γ and IL-4 by ELISA method. Statistical analysis with alternative test non-parametric Mann Whitney. IFN-γ secretion in patients with active pulmonary TB group (6700 pg / ml) was higher than the latent (6000 pg / ml) after stimulation by antigen fusion EC610, but not significant (p = 0.769). While the secretion of IL-4 levels (180 and 60 pg / ml) there was a significant difference between the groups (p = 0.000).